Adherence, invasion and intracellular survival between Pasteurella multocida B:2 and its derivatives towards bovine aortic endothelial cell - Mohd Kamal, Nur Iqmaliza Akmal (2017)
Pasteurella multocida B:2 causes bovine haemorrhagic septicaemia leading to acute fatality in cattle and buffaloes. This bacterium spread rapidly from the respiratory tract into the bloodstream causing death within 24 hours. Countries where the disease is endemic resort to routine prophylactic vaccination. However, it failed to contain and eradicate the disease. Liveattenuated vaccines have the advantage of a natural route of entry to the host which allows targeting of immunomodulatory factors to the same sites of the immune system as occurs in the natural infection and achieves longer lasting immunity.Pasteurella multocida B:2 GDH7 is an attenuated derivative of the wild-type P. multocida B:2 isolated from a previous outbreak in Malaysia, that upon intranasal administration is an efficient vaccine for HS. This strain was genetically modified by the disruption of the wild-type gdhA gene with the insertion of a kanamycin cassette. This resulted in an interference of bacterial metabolism hence arresting its pathogenicity. This study primarily aims to investigate the potential of P. multocida B:2 GDH7 strain as a delivery vehicle for DNA vaccine applications. Following this, an investigation on the adherence, invasion and intracellular survival of the bacterial strains within the bovine aortic endothelial cell line (BAEC) were carried out. The parent strain and another mutant strain from Sri Lanka, P. multocida B:2 JRMT12 were used as control. The potential vaccine strain, P. multocida B:2 GDH7, was significantly better at adhering to and invading BAEC (p ≤ 0.05) compared to the wild-type. Moreover, this strain was observed to survive intracellularly 7 hours post-treatment, although a steady decline in viability was noted with time. A dual reporter plasmid, pSRGM that expresses red fluorescent protein (RFP) from a constitutive prokaryotic promoter within P. multocida B:2 and green fluorescent protein (GFP) from a constitutive eukaryotic promoter within mammalian cells was subsequently transformed into P. multocida B:2 GDH7. This construct was used to colocalize the bacteria when moving from the extracellular environment into the intracellular compartment of the mammalian cells. Intracellular trafficking of the vaccine strain, P. multocida B:2 GDH7 was visualized by tracking the reporter proteins via confocal laser scanning microscopy (CLSM). Pasteurella multocida B:2 GDH7 was found intracellularly of the mammalian cells and manage to release the reporter plasmid into the cytoplasm and allows GFP expression from the mammalian host at 3 h post-treatment. The ability of P. multocida B:2 GDH7 to model a bactofection represents the possibility for this potential vaccine strain to be used as a delivery vehicle for DNA vaccine. From this study, P. multocida B:2 GDH7, showed to be a promising candidate as a potential delivery vehicle for DNA vaccine.